The Influence of Leadership Style and Organizational Culture on Teacher Performance at SMA Negeri 2 Binjai - Adrian Sahputra; Soulthan Saladin Batubara; Ahmad Aswan Waruwu (Journal of Research in Social Science and Humanities, 2025)
Teachers as the spearhead of educational implementation are required to have optimal performance to achieve educational goals. This study aims to analyze the influence of principal leadership style and organizational culture on teacher performance at SMA Negeri 2 Binjai. This research employed a quantitative approach with an associative design. The population consisted of 81 teachers, all of whom were selected as samples using a total sampling technique. Data were collected through questionnaires measured on a Likert scale and analyzed using multiple linear regression with SPSS. The results show that leadership style and organizational culture partially and simultaneously have a positive and significant effect on teacher performance. These findings indicate that effective school leadership and a conducive organizational culture play an important role in improving teacher performance